CHARACTERIZATION AND POTENTIAL UTILIZATION OF STRING BAMBOO (GIGANTOCHLOA APUS) - Oliver Marasigan; Shereyl A. Daguinod (BIOTROPIA, 2025)
HIGHLIGHTS- Gigantochloa apus shows strong potential for structural and engineered uses.- Axial and nodal variations significantly affect bamboo fiber anatomy.- Relative density and strength make G. apus suitable for construction and furniture.- Derived fiber ratios indicate limited papermaking suitability.- G. apus offers broad utilization potential for sustainable industriesABSTRACTThis study assessed the morphological, anatomical, derived ratio, and physico-mechanical properties of string bamboo (Gigantochloa apus [Schult.f.] Kurz ex Munro) grown in Baguio City, Philippines, to establish comprehensive property data and explore potential applications. Six mature culms were sampled and tested for its properties following the IAWA, ISO, and ASTM standards. Results revealed that culm diameter and wall thickness decreased significantly by 37.30% and 46.60%, respectively, toward the top portion. Anatomical analysis showed significant decreases in fiber length, fiber diameter, lumen diameter, and cell wall thickness by 15.33%, 13.86%, 24.05%, and 8.43%, respectively, from bottom to top. All derived ratios varied significantly between the node and internode portions. The node portion exhibited higher values for cell wall fraction, Runkel ratio, Muhlsteph ratio, rigidity coefficient, and Luce’s shape factor. Radial and volumetric shrinkage decreased by 29.47% and 31.01%, respectively, toward the top, while shear strength dropped by 47.20%. In contrast, basic relative density, modulus of rupture, modulus of elasticity, and compression strength showed no significant variation along the culm. These findings highlight that G. apus is suitable for diverse applications including furniture, handicrafts, construction, engineered bamboo, and biomass products.